1985
DOI: 10.1083/jcb.101.6.2245
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of benzo(a)pyrene induction of alpha-human chorionic gonadotropin gene expression in human lung tumor cells.

Abstract: Human lung cells (ChaGo) derived from a bronchogenic carcinoma synthesize and secrete in the culture medium the alpha subunit of the glycoprotein hormone, human chorionic gonadotropin (alpha-hCG). The synthesis of alpha-hCG by ChaGo cells could be further stimulated by treatment with sublethal concentrations of the polycyclic aromatic hydrocarbons (PAHs), benzo(a)pyrene (gaP), or dimethylbenzanthracene. The production of alpha-hCG could be correlated to the levels of alpha-hCG-specific mRNA sequences in contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
3
9
0
Order By: Relevance
“…1 C demonstrate that of high molecular weight alpha-hCG-specific nuclear RNA sequences between control and PAH-treated cells. The observed increased levels of alpha-hCG mRNA sequences in BaP or DMBA-treated ChaGo cells detected by Northern blot analysis not only confirm the previously reported results obtained by dot hybridization analysis (14), but also characterize the molecular sizes of alpha-hCG-specific cytoplasmic and nuclear RNA transcripts. The increased level of alpha-hCG production in PAH-treated cells can thus be correlated to the corresponding elevated levels of different species of cytoplasmic and nuclear alpha-hCG mRNA sequences.…”
Section: Levels Of Cytoplasmic and Nuclear Alpha-hcg Rna In Control Asupporting
confidence: 78%
See 4 more Smart Citations
“…1 C demonstrate that of high molecular weight alpha-hCG-specific nuclear RNA sequences between control and PAH-treated cells. The observed increased levels of alpha-hCG mRNA sequences in BaP or DMBA-treated ChaGo cells detected by Northern blot analysis not only confirm the previously reported results obtained by dot hybridization analysis (14), but also characterize the molecular sizes of alpha-hCG-specific cytoplasmic and nuclear RNA transcripts. The increased level of alpha-hCG production in PAH-treated cells can thus be correlated to the corresponding elevated levels of different species of cytoplasmic and nuclear alpha-hCG mRNA sequences.…”
Section: Levels Of Cytoplasmic and Nuclear Alpha-hcg Rna In Control Asupporting
confidence: 78%
“…As stated above, either BaP or DMBA treatment of ChaGo cells increased the levels of cytoplasmic alpha-hCG mRNA sequences. We have previously reported that DMBA stimulation of alpha-hCG synthesis was somewhat higher than that observed after BaP treatment of ChaGo cells (14). This was further substantiated by the results presented in It is believed that the cytotoxic effects of chemical carcinogens are due to their genotoxic/DNA damaging effects caused by reactive metabolites of BaP.…”
Section: Bap Metabolism and Induction Of The Alpha-hcg Gene Expressiosupporting
confidence: 76%
See 3 more Smart Citations